BFA SHOW - 2018: A window to the future - Chitrakar, Madan (SIRJANĀ – A Journal Of Arts and Art Education, 2018)
Graduation Show 2018 proved once again, to be a window to unveil our achievements - made within past one academic year: and to our students, the first occasion to make a public appearance. The Paintings and Sculptures remained a microcosm of academic skills mixed with the ability to transcend into a creative world - to narrate personal feelings, then to respond artistically in art. Moreover, it also displayed their ability to recreate works based on the centuries’ old traditional forms and the motifs. In the Graphic Communications section, our young graduates could assert they are competent and capable to cope with any professional challenges – as needed in any industrial and a modern society.